Service delivery characteristics preferences and trade-offs for long-acting injectable pre-exposure prophylaxis among female students in tertiary institutions in South Africa: A discrete choice experiment - Patience Shamu; Saiqa Mullick; Nicola J. Christofides (Global Public Health)
Oral pre-exposure prophylaxis (PrEP) for HIV prevention promises women more control over HIV prevention. To alleviate low PrEP uptake, rolling out long-acting PrEP methods could increase uptake in women’s preferred ways. The study sought to determine injectable PrEP service delivery characteristics that effectively meet young women’s service needs. In 2023, we conducted a discrete choice experiment in South African tertiary institutions. We recruited and interviewed 400 female students mostly queuing for sexual health services. Data were analysed using mixed logit and latent class models.Young women strongly prefer using campus clinics to non-campus clinics and returning to the facility for product information and its side effects to using a chatbot [OR  = 1.07, CI: 1.02, 1.13]. Also, compared to getting a free service, students were prepared to pay R50 ($2.90) [OR = 1.14, CI: 1.05, 1.25]. Three classes emerged from the latent class model and these differed by background characteristics like age group and study year. Receiving PrEP through campus services from sensitive, PrEP providers and providing accurate information on side effects was preferred by students over community-based primary health care clinics with public health nurses. PrEP-trained providers should provide PrEP services as young people prefer returning to facilities for further youth-friendly support.